A siker titka: A magánerős modernizáció (Soltvadkert) - Fertő, Imre; Lénárt, Zsolt; Maurer, György; Winkler, Tamás (Tér és Társadalom, 1990)
Soltvadkert, a large village of 8,000 inhabitants in Bács-Kiskun county, is located in the former Kiskőrös district, 120 km south-southeast of Budapest. The village was founded by Protestant German-speaking settlers in the 1700s. They soon became Magyarized but the Protestant belief remained important in spite of strong attempts at reconvertion to catholicism. The soil in Soltvadkert (as well as in the whole district) is a mere sandy soil, thus grape and wine-growing has played a major role in farming from the very beginning. Another important impact of the poor soil was that no latifundia were formed within the area of the village. At the end of the last century (when phylloxera devastated most of Hungary’s historic vineyards) there was an increasing demand for wine grown on sandy soil. Soltvadkert was in a privileged position for two reasons: it hada railway as early as in 1882, and centuries old traditions in viticulture. These were the major reasons explaining the rising development of the village, making wittingly use of the boom, at the turn of the century. Between the two wars capitalist farms appeared which introduced new technologies, new sorts of wine, new tools and other means in grapeand wine-growing. Urban-like lifestyles and social roles were on the make in Soltvadkert. This process was interrupted by the Stalinist agrarian policy during the 1950s which also wore down Soltvadkert but (because it had a larger material and cultural capital than most Hungarian villages) it arrived in a better shape at the 1956 turning point. The post-1957 economic management created, though temporarily, better conditions for agricultural production which was then made definitely impossible by the 1959-61 collectivization. At the end of the 1960s, luckily for Soltvadkert, collectivization here was limited: a so-called specialized cooperative was only formed. (Besides strong opposition from the part of the peasant strata, local officials also made important contributions to this luck.) The concept of specialized cooperatives developed in 1958-59 served the purpuse of mobilizing local energies: in the (inal stage of collectivization, central material resources got exhausted, thus more emphasis was laid on those forms of collectivization which relied more on local resources. Specialized cooperatives (spec. coops) have been essentially different from Hungarian cooperatives in general. The most important differences characteristic of spec. coops are the following: An entrance fee was levied which was not the case with cooperatives; Certain intensive land uses were not drawn into collective farming; owners cultivated the land individually. This segment is called (individual) members’ farms; The means of production used in members’ farms remained in individual ownership and use; Payments in cash and production for marketing have prevailed in spec. coops from the very beginning; 10% of the return from selling grapes and wine produced in members’ farms had to be payed by individual members to the spec. coop which (without any reduction for tax) increased its development fund. In this way a political compromise actually united the classical agricultural cooperative (family farm plus a coop centre which coordinates collecting, purchasing, processing and selling) and the artiel type of cooperative (collective farming). In our opinion it is vital that in such a construction the members’ farms could be (and in Soltvadkert they actually were) apt to become viable on their own, independently, if necessary, from the spec. coop itself already at the moment of their birth. (This was not the case with household plots of coop members in general.) This fact serves as a basis for genuine joint interests between members (particularly those with strong farms) and leaders since members’ farms not only produce the capital needed for their own modernization but, due to the above mentioned 10% contribution, they are important factors of dinamizing the collective farm of the cooperative. On the other hand, the spec. coop benefited the family farms in the period of hostile political atmosphere: It provided a legal ground for their existence and thus prevented members’ farms from the periodical attemps at collectivization which was equivalent to nationalization. It played the role of a buffer between market-oriented farming (the members’ farms) requiring and inferring a marker economy and the actual economic environment which was hostile to this or was „just" neglecting this very fact. Developments in Soltvadkert are prevented here as a model, not because the efficiency ol production is above national average but because the modernization generated by members’ farms is not limited to economic development in a narrow sense but involves the modernization of infrastructure and motivated an educational strategy linked to individual farming: the use of knowledge in members’ farms has become a factor to be considered when deciding on future trade or profession. As a result of all this, a mobile social structure has been created by now which is characterized by ample interactions and the variety of social roles. The sectret of this success is to be found in individual modernization (of members’ farms) indicated in the title.